2014
DOI: 10.1128/jcm.00216-14
|View full text |Cite
|
Sign up to set email alerts
|

Misidentification of Neosartorya pseudofischeri as Aspergillus fumigatus in a Lung Transplant Patient

Abstract: We present a case of disseminated Neosartorya pseudofischeri infection in a bilateral lung transplant patient with cystic fibrosis. The organism was originally misidentified from respiratory specimens as Aspergillus fumigatus using colonial and microscopic morphology. DNA sequencing subsequently identified the organism correctly as N. pseudofischeri. CASE REPORTA 36-year-old female with cystic fibrosis underwent bilateral lung transplantation in October 2011. Prior to her transplant, she had frequent respirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 13 publications
(19 reference statements)
1
8
0
2
Order By: Relevance
“…[68][69][70] These include A. lentulus, A. felis, A. parafelis, A. pseudofelis, A. pseudoviridinutans, N. pseudofischeri, and N. udagawae. 66,[71][72][73][74] Numerous case reports of clinical failures in patients treated with antifungals for infections misidentified as A. fumigatus can be found in the literature. 64,[69][70][71]74,75 Unfortunately, species identification by molecular and morphologic characteristics requires a culture, and in many patients with invasive aspergillosis recovery of the infecting organism is not possible.…”
Section: Importance Of Species Determinationmentioning
confidence: 99%
“…[68][69][70] These include A. lentulus, A. felis, A. parafelis, A. pseudofelis, A. pseudoviridinutans, N. pseudofischeri, and N. udagawae. 66,[71][72][73][74] Numerous case reports of clinical failures in patients treated with antifungals for infections misidentified as A. fumigatus can be found in the literature. 64,[69][70][71]74,75 Unfortunately, species identification by molecular and morphologic characteristics requires a culture, and in many patients with invasive aspergillosis recovery of the infecting organism is not possible.…”
Section: Importance Of Species Determinationmentioning
confidence: 99%
“…A genuine need for investment in prospective placebo-controlled trials to evaluate antifungal therapies in a wide range of clinical settings is now therefore justifiable. This would begin to address [3,28]. This has been reported in the literature and impacts on our understanding of the "real" incidence of colonization and infection in CF populations.…”
Section: Unresolved Questionsmentioning
confidence: 94%
“…This includes yeast, yeastlike, and filamentous fungi. Genetic technology has revealed that many fungi that were previously reported to genus and species were indeed misidentified, leading mycologists to re-examine past cases to determine the prevalence of certain fungi in certain disease states [37][38][39][40][41][42][43].…”
Section: Microbiologymentioning
confidence: 99%